Molecular epidemiology of type 1 and 2 dengue viruses in Brazil from 1988 to 2001 - Pires Neto,R.J. (2005)
Dengue is a mosquito-borne viral infection that in recent decades has become a major international public health concern. Epidemic dengue fever reemerged in Brazil in 1981. Since 1990 more than one dengue virus serotype has been circulating in this tropical country and increasing rates of dengue hemorrhagic fever and dengue shock syndrome have been detected every year. Some evidence supports the association between the introduction of a new serotype and/or genotype in a region and the appearance of dengue hemorrhagic fever. In order to study the evolutionary relationships and possible detection of the introduction of new dengue virus genotypes in Brazil in the last years, we analyzed partial nucleotide sequences of 52 Brazilian samples of both dengue type 1 and dengue type 2 isolated from 1988 to 2001 from highly endemic regions. A 240-nucleotide-long sequence from the envelope/nonstructural protein 1 gene junction was used for phylogenetic analysis. After comparing the nucleotide sequences originally obtained in this study to those previously studied by others, and analyzing the phylogenetic trees, we conclude that, after the initial introduction of the currently circulating dengue-1 and dengue-2 genotypes in Brazil, there has been no evidence of introduction of new genotypes since 1988. The increasing number of dengue hemorrhagic fever cases seen in Brazil in the last years is probably associated with secondary infections or with the introduction of new serotypes but not with the introduction of new genotypes.